TERRORISM IN CHECHNIA: DEFINITION OF THE PHENOMENON AND ITS EXPLANATION - MARKEDONOV, Sergey (CENTRAL ASIA AND THE CAUCASUS, 2004)
Much has been written about terrorism; albeit a phenomenon that seems to have been studied in detail, it remains sinister, enigmatic, irrational, and defying complete understanding.”1 It is hard to deny this opinion of prominent Russian Orientalist Georgy Mirskiy: it can be applied both to the theoretical-methodological side of the phenomenon and to a case study of terrorism in Chechnia. In the past ten years the concept of terrorism has been closely associated with Chechnia; this definition, as well as the much more recent coinage, counter-terrorist operation, have been accepted by the Russian expert community to the extent that they require no further explanation.